A Comprehensive Review and Analysis of Blockchain-Based Security Solutions for Cloud Computing Ecosystems - Jameel, Noor Ghazi M.; Rashid, Zryan Najat; Şengür, Abdulkadir (Kurdistan Journal of Applied Research, 2025)
Cloud computing is a rapidly evolving technology that defines a modern digital computing framework and business approach for utilizing software and hardware resources. While it provides numerous advantages, it also brings with it considerable security risks and challenges. This paper discusses cloud computing and blockchain technology with a focus on the security implications of integrating these two technologies for solving three security issues in the cloud environment. Three major security domains—data security, identity authentication and management, and access control—have been analyzed through an in-depth review of recent studies to evaluate the strengths of integrating both technologies, identify existing limitations, and propose suggestions for future research directions. Relevant literature was retrieved from five major scientific databases: Google Scholar, ScienceDirect, IEEE Xplore, Scopus, and Web of Science. The selection of studies was guided by predefined research questions and specific inclusion and exclusion criteria. The findings reveal that the combination of blockchain and cloud computing establishes a new era of enhanced security. This fusion of blockchain and cloud computing represents the most promising path forward, offering robust security with decentralization and delivering significant advancements in authentication, authorization, data integrity, and privacy protection. This approach will open up vast opportunities in various sectors like healthcare, business, supply chain, and industry due to its guaranteed data security, improved efficiency, and reduced costs.  Future research areas need further investigation, such as designing innovative consensus mechanisms to boost scalability and leveraging artificial intelligence and machine learning to improve security and privacy by incorporating blockchain technology into cloud environments.